Charlotte Everett Hopkins collection of National Civic Federation. Woman's Department. District of Columbia Section records - Hopkins, Charlotte Everett; Council of National Defense (Washington, D.C.). Woman's Committee. Woman's Committee records; National Civic Federation. Woman's Department. District of Columbia Section
Correspondence, minutes, reports, circulars, clippings, printed matter, and other papers relating chiefly to Hopkins's activities as chairman of the National Civic Federation Woman's Department District of Columbia Section. Subjects include municipal reform efforts in the areas of war relief, housing, garbage collection, health, diet, pure milk, juvenile delinquency, playgrounds, and working conditions of District citizens. Subject file includes circulars, minutes, and reports from the National Civic Federation and the Woman's Committee of the Council of National Defense (Washington, D.C.). Authored by Carrie Chapman Catt, Anna Howard Shaw, and others. Correspondents include Steven B. Ayres, Gertrude Beeks, Nannie Helen Burroughs, Leonidas Carstarphen Dyer, Jacob H. Gallinger, Natalie Harris Hammond, Thomas Jesse Jones, Ruth Hanna McCormick Simms, and Maude A.K. Wetmore. Organizational correspondents include the Alley Improvement Association, Washington, D.C.; Associated Charities of the District of Columbia; Colored Settlement Association (Washington, D.C.); Council of National Defense (Washington, D.C.) Woman's Committee; National American Woman Suffrage Association; National Committee on Prison Labor; and the National Surgical Dressings Committee, Washington, D.C.
Civic leader, philanthropist, and social reformer. Full name: Charlotte Everett Wise Hopkins; also, Mrs. Archibald Hopkins. Born 1851; died 1935.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ayres, Steven B. -- 1861-1929 -- Correspondence; Beeks, Gertrude, -- 1867- -- Correspondence; Burroughs, Nannie Helen, -- 1879-1961 -- Correspondence; Catt, Carrie Chapman, -- 1859-1947.; Dyer, Leonidas Carstarphen, -- 1871-1957 -- Correspondence; Gallinger, Jacob H. -- 1837-1918 -- Correspondence; Hammond, Natalie Harris, -- 1861-1931 -- Correspondence; Jones, Thomas Jesse, -- 1873-1950 -- Correspondence; Shaw, Anna Howard, -- 1847-1919.; Simms, Ruth Hanna McCormick, -- 1880-1944 -- Correspondence; Wetmore, Maude A. K. -- 1873-1951 -- Correspondence; Alley Improvement Association -- Correspondence; Associated Charities of the District of Columbia -- Correspondence; Colored Settlement Association (Washington, D.C.) -- Correspondence; Council of National Defense (Washington, D.C.). -- Woman's Committee -- Correspondence; National American Woman Suffrage Association -- Correspondence; National Committee on Prison Labor -- Correspondence; National Surgical Dressings Committee -- Correspondence; Health; Housing -- Washington (D.C.); Juvenile delinquency -- Washington (D.C.); Milk; Municipal government -- Washington (D.C.); Playgrounds -- Washington (D.C.); Refuse collection -- Washington (D.C.); War relief; Work environment -- Washington (D.C.); World War, 1914-1918 -- Civilian relief -- United States; Civic leaders; Philanthropists; Social reformers